O recurso à ciência no processo : a prova científica no direito processual civil brasileiro - Sonegheti, Victor (2012)
The use of science in the process is not exactly new, on the contrary, expert evidence has been long used to adduce expertise of technical or scientific nature into the process. What can be considered the dimension currently achieved by the ingress of scientific knowledge in the judicial process, especially after the scientific boom of the second half of the twentieth century, that we are now witnessing a degree of integration between science and law never seen before. It is precisely in this context of integration (and interdependence) between law and science that the issue of scientific evidence is located. This study aims to analyze and discuss the specific issues of scientific evidence, seeking to clarify some of the big questions hanging over the subject, starting with the concept and delineation of what constitutes scientific evidence, outlining its features based on the studies of the doctrine, passing to the study of its admissibility in the process through a comparative study with American jurisprudence, coming finally to the difficult issues regarding their control and valuation by the magistrate and its controversial relationship with the res judicata. The aim is also to delineate an overview of the current state of scientific evidence in the Brazilian legal order by examining the tools and assessment procedures for the admissibility of evidence enshrined in existing legislation are sufficient and appropriate to deal with scientific evidence.